Review: Perpetual Motion: Dance, Digital Cultures, and the Common by Harmony Bench (2020) - Price, Jaleea (The International Journal of Screendance, 2020)
Perpetual Motion: Dance, Digital Cultures, and the Common takes the reader on a journey through a collection of digital dance works that cumulatively reveal a rich, and ongoing, interplay between dance and digital media. Available for purchase as a book and as an open-access download, Perpetual Motion details an historical evolution of dance's engagement within shared digital media experiences, focusing on the period from 1996 to 2016. As a reader, I quickly found within these pages a personal connectivity and, in these isolating times, a renewed membership into the global, online corporeal community. With myriad works (re)discovered in each chapter, Perpetual Motion shows us the global impact dance and digital media have had upon each other through shared social relationships and interactions, both on- and off-screen.